Synthesis, spectroscopic, X-ray diffraction and tautomeric properties of 5-(diethylamino)-2-((2-(5-(3-methyl-3-phenylcyclobutyl)-6H-1,3,4-thiadiazin-2yl)hydrazono)methyl)phenol: A combined experimental and theoretical study - Cukurovali, Alaaddin; Karakurt, Tuncay (Elsevier, 2019)
In this study, 5-(diethylamino)-2-((2- (5- (3-methyl-3-phenylcyclobutyl) -6H-1,3,4-thiadiazin-2yl) hydrazono)methyl)phenol single crystal, which is Schiff base, was synthesized. The synthesized crystal structure was confirmed by X-ray diffraction, IR, H-1 and C-13 NMR spectroscopic techniques. The molecules are linked by two intermolecular (C-H center dot center dot center dot O and N-H center dot center dot center dot N) and an intramolecular (O-H center dot center dot center dot N) hydrogen bonds. It was observed that the title compound can be in two tautomeric structures. The geometric parameters, C-13-, H-1- NMR and IR spectra and frontier molecular orbitals (FMO) of the title crystal were optimized using the Gaussian 09 package program with DFT theory, as well as the tautomer structures were compared with the IRC (Intrinsic Reaction Coordinate) analysis method. In addition, the lattice energies of two tautomer structures were calculated by Quantum-Espresso program using periodic boundary conditions (PBC). All theoretical and experimental studies were executed on two tautomeric structures. Theoretical calculations were made to compare with experimental results. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Gaussian 09; X-ray; Tautomeric; PBC; Quantum-Espresso